The Saint-Non Expedition in Eastern Sicily: from Messina to Catania between Landscape and Antiquity - Francesca Passalacqua (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2019)
In the second half of the 18th century, renowned archaeological sites and exuberant nature attracted travellers from many parts of Europe to Sicily. They wanted to end their Grand Tour on the Island in search of the picturesque and sublime cities, ruins and landscapes of a mythical, wild, Mediterranean territory. The fourth volume of the Voyage pittoresque ou description des royaumes de Naples et de Sicile by Jean-Claude Richard Abbé de Saint-Non, published in two parts in 1785 and 1786, marked the arrival point of the artistic, archaeological and naturalistic interests of many travellers who arrived on the Island in those years. These were symbolically represented by Dominique Vivant Denon, appointed by Saint-Non to describe the places and monuments in writing, which had also been described through the images of the artists who had accompanied him during the trip. The abbot, dismantled and reassembled the texts of the diary of Denon, also in the fourth volume, as he had done in the previous three volumes, published in original form only at a later time, and only in the case of Sicily (Voyage in Sicile, 1788). Denon’s diary, published ten years after its original editorship and without the full-bodied historical insights later added by Saint-Non, kept the freshness of the author’s travel impressions intact. This diary will be the main reference of this paper that intends to retrace the journey from Messina to Catania, along the traces of the roads of eastern Sicily, also through the images handed down by the artists who accompanied him: the landscape painter Claude-Louis Châtelet and the architects Louis-Jean Desprez and Jean-Augustin Renard.